2009
DOI: 10.1007/s12187-009-9042-x
|View full text |Cite
|
Sign up to set email alerts
|

Accentuating the Negative: The Mismatch Between Public Perception of Child Well-being and Official Statistics

Abstract: This paper reports findings from a series of polls designed to ascertain how well the American public understands the circumstances, characteristics, and living conditions of American children. We compare poll responses to official statistics to assess the accuracy of the public's perceptions. With few exceptions, the results suggest a large gap between the public's perception of children and official statistics and highlight a second finding-primarily, where misperceptions exist the public tends to perceive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Finally, a handful of papers address the feasibility and added‐value to research of the integration of children's perspective on their own situation (Norrby and others, ). Child well‐being 's subjective nature is thus here more or less given; evidence leading in that direction relates for instance to the discrepancy existing between a population's perspective on children's level of well‐being and its valuation by official statistics (Guzman and others, ). Thus, the object of debates relates to the need for appropriate methods of research (Crivello and others, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a handful of papers address the feasibility and added‐value to research of the integration of children's perspective on their own situation (Norrby and others, ). Child well‐being 's subjective nature is thus here more or less given; evidence leading in that direction relates for instance to the discrepancy existing between a population's perspective on children's level of well‐being and its valuation by official statistics (Guzman and others, ). Thus, the object of debates relates to the need for appropriate methods of research (Crivello and others, ).…”
Section: Resultsmentioning
confidence: 99%
“…Although most research projects present a panel of objective measures, this objectification does not take account of the inner subjectivity of well‐being . Indeed, its subjective nature has been demonstrated through the discrepancies existing between people's perception of children's circumstances and children's perception of their own circumstances, thereby defending the integration of children's own perspective (Ben‐Arieh and others, ; Fox and others, ; Guzman and others, ).…”
Section: Five Structural Theoretical Axesmentioning
confidence: 99%
“…Druhou osou je subjektivní a objektivní měření, kdy objektivní měření well-beingu nemusí vždy být v souladu s perspektivou dětí a jejich vnímáním vlastní situace (např. Guzman et al, 2009). Třetí osou je binarita well-beingu jako stavu nebo procesu, což odpovídá pojetí, zda jde spíše o hédonickou definici, nebo tu eudaimonickou.…”
Section: Aktuální Dění V čRunclassified
“…A survey which asked a representative sample of American adults about several dimensions of child well-being, found that there were often large differences between the public's perception and the official data. Guzman et al (2009) found, for example, less than half the adults could correctly select the child poverty rate from three alternatives. Only 5 % of adults knew roughly what percent of children in the United States lacked health insurance.…”
Section: Communication Issuesmentioning
confidence: 99%
“…Only 5 % of adults knew roughly what percent of children in the United States lacked health insurance. Moreover, when adults held misperceptions about the state of child well-being, they tended to accentuate the negative (Guzman et al 2009;The Public Agenda 1997).…”
Section: Communication Issuesmentioning
confidence: 99%